Implementasi Program Mama Berta Joko Tingting dalam Penanganan Stunting di Kalurahan Sendangrejo Kapanewon Minggir - Nabila Suswitika Nandago; Muhammad Salisul Khakim (Bahasa Indonesia, 2025)
Astunting is still a problem with the main focus of imporving nutrition in the world. Indonesia is one of the countries with a fairly high prevalence of stunting due to the economic conditions of the poor community so that they cannot meet the nutritional needs of toddlers and pregnant woment. The purpose of this study was to determine the implementation of the Mama Berta Joko Tingting Program in handling stunting in Sendangrejo Village which was attended by mothers and stunted toddlers from Sendangrejo Village. The study focused on Sendangrejo Village which has the largest number of stunted toddlers in the last 2 years in Minggir District. This study uses qualitative descriptive where the research was conducted in the field directly and was made in narrative descriptive which describes events in real and as the are. The result of this study can be conclude that most mothers of toddlers are very enthusiastic about participating in the program and this program has been proven to increase the height and weight of toddlers. However, in this activity there are still challenges and obstacles, even though motivation and education have been cariied out by related parties.